Substitusi Tepung Kacang Hijau dan Bubuk Cabai Merah pada Pembuatan Cheese Bread Stick - Tri Rettagung Diana; Ralda Iftaliana (Garina, 2021)
The purpose of this study is 1) Knowing the right recipe for cheese bread stick products susbtitusi green bean flour and red chili powder; 2) Knowing the difference in the quality of cheese bread stick substitution green bean flour and red chili powder with different percentages seen from the aspect of color, aroma, taste and texture; 3) Know the level of people's fondness for cheese bread stick substitution green bean flour and red chili powder. This research uses literature methods, experiments, documentation, hedonic tests and data analysis. The experiment was done three times. The number of panelists who filled out the questionnaire was 35 untrained panelists. The results showed that the most preferred cheese bead stick product and red chili powder is a cheese bread stick product with a percentage of green bean flour substitution as much as 50%. The most preferred green bean flour substitute cheese bread stick recipe and red chili powder include 50 g wheat flour, 50 g green bean flour, 40 g edam cheese, 40 g margarine, 24 g egg whites, 2.5 g red chilli powder, 1 g salt and 0.25 g baking soda.